Respuesta :

Answer:

b. g(x) = ƒ(3x)

Step-by-step explanation:

We can use the graph to find the transformation which has been performed to obtain g.

g(x) is more stretched than x which means the function values are multiplied by some integer to obtain g(x). This eliminates the options a and d.

Now to check which factor is used to transform the function f(x) we can divide the x-coordinates of the points of new and old function.

So,

6/2 = 3

-6/-2 = 3

The function is stretched by a factor of 3.

Hence, the correct answer is:

b. g(x) = ƒ(3x)  ..

ACCESS MORE